The Approach of Sheikh Ibn Uthaymeen in Responding to Specious Arguments through the Interpretation of Surah Al-Baqarah: An Analytical Study: منهج الشيخ ابن عثيمين في الرد على الشبهات من خلال تفسير سورة البقرة: دراسة تحليلية - Sameer Mahoob Saleh Qassem (Mauriduna : Journal of Islamic Studies, 2025)
Starting from the researcher’s interest in the interpretation of the Quran and in refuting the doubts raised about it, the researcher decided to address a topic related to refuting the doubts found in the interpretation of Surah Al-Baqarah, relying on the methodology adopted by Imam Ibn Uthaymin in his works. The choice of this topic is due to its great importance in clarifying the scientific method of dealing with theological and intellectual doubts facing the contemporary Muslim, as well as the scholarly, critical, and precise dimensions found in Ibn Uthaymin’s interpretation. The researcher aims to highlight Ibn Uthaymin’s efforts in refuting doubts, analyzing their content, clarifying the methods of response he employed, and examining how consistent they are with the Salafi methodology in exegesis. The researcher relied on the analytical inductive approach in dealing with the topic, collecting the passages related to doubts from the interpretation of Surah Al-Baqarah, analyzing them, and extracting the principles and methods used in addressing them. Among the most significant findings reached by the researcher is that Ibn Uthaymin’s approach — may Allah have mercy on him — was characterized by a balance between scholarly precision and clarity in presentation, making his refutation of doubts a scientific model that can be utilized in the fields of Quranic exegesis, creed, and Islamic preaching.